Temporal causality between energy consumption and income in six Asian emerging countries - Rafiq, S.; Salim, Ruhul (Duncker & Humblot GmbH, 12165 Berlin, 2009)
This article examines the short- and long-run causal relationship between energy consumptionand GDP of six emerging economies of Asia. Based on cointegration and vectorerror correction modeling the empirical results show that there exists a unidirectional shortandlong-run causality running from energy consumption to GDP for China, a unidirectionalshort-run causality from output to energy consumption for India, whilst a bi-directionalshort-run causality for Thailand. Neutrality between energy consumption and income isfound for Indonesia, Malaysia and Philippines. Following causality results India may contributeto the fight against global warming directly implementing energy conservation measures.For China, where causality runs from energy consumption to output, the country shouldfocus on technological developments and mitigation policies. Since a bi-directional causalityis found in Thailand, a balanced combination of alternative policies seems to be appropriate.Nevertheless, all the countries may initiate environmental policies aimed at decreasing energyintensity, increasing energy efficiency, developing a market for emission trading.